Language ideologies and the politics of language in post-colonial Africa - Wolff, Ekkehard (Stellenbosch Papers in Linguistics Plus, 2017)
Academic and political discourse on language policies and nation-building in post-colonial Africa is highly ideologised. Facing two extreme ideological positions, namely what one might call ‘19th century European nation state-ideology’ vs ‘20th/21st century African Renaissance-ideology’, language planners and decision makers in Africa are caught between a rock and a hard place. The paper begins by sketching out salient differences between the two sets of ideological positions: (1) Ideologies based on European historical-cultural experience which gave rise to a particular ‘Western’ mind-set; this mind-set is built on convictions regarding European exceptionalism and on notions linked to linguistically and culturally homogenous nations. (2) Ideologies informed by anti-colonialist struggle and anti-imperialist philosophy which, further, rest on the recognition of sociolinguistic realities in Africa, the latter being characterised by extreme ethnolinguistic plurality and diversity. While the first set continues to have considerable impact on academic and political discourse in terms of prevailing Eurocentric perspective and attitudes infested by Orientalism, the second is rooted in idealistic positions relating to Universal Human Linguistic Rights and notions of African Identity and Personality. Such strategies have been and still are widely discussed in academic and political circles across Africa. A third position is that of bridging this ideological gap by advocating multilingual policies which would combine indigenous languages of local and regional relevance with imported languages of global reach towards the strategic goal of mother tongue-based multilingualism (MTBML). The ongoing highly controversial debate, however, tends to overlook the fact that MTBML is exactly the ‘language(s)-in-education policy’ that most so-called developed countries, including the former colonial powers of Europe, have long since installed to best serve their own political interests and economic progress.